Prescription patterns of enzyme-containing products in South Africa over a 2-year period - Truter, Ilse (South African Journal of Science, 2014)
Enzymes are traded in five categories, namely medical (intervention), diagnostic (detection and quantification), molecular biology, biofuel and industrial. Therapeutic enzymes have been investigated for different uses, for example, for the treatment of genetic disorders, blood clotting disorders, cancer and infectious diseases and for burn debridement. No studies on the prescription of enzyme-containing products in South Africa could be found. Enzymes are classified in the Monthly Index of Medical Specialities under digestants, enzymes and fibrinolytics. The primary aim of this study was to investigate the prescription patterns and cost of enzyme-containing products in South Africa. A private health-care medicines claims database for 2010 and 2011 of approximately 4.5 million records was analysed retrospectively. Enzyme-containing products constituted a small percentage of medical insurance claims (only 0.02% of approximately 4.5 million claims for products and procedures), yet they were relatively expensive. A total of 906 products was prescribed at a cost of almost ZAR2 million over the 2 years. Hyaluronidase was the most frequently prescribed (60.04%), followed by pancreatin-containing products (34.66%). Pancreatin (lipase/ protease/amylase) is primarily used in the management of pancreatic exocrine insufficiency. The average cost per hyaluronidase prescription paid by the medical insurance schemes was ZAR280. Other enzyme-containing products prescribed were imiglucerase, alteplase and tenecteplase. Imiglucerase was overall the most expensive. Alteplase, tenecteplase and streptokinase are antithrombotic enzymes that are used in the treatment of acute myocardial infarction or ischaemic stroke. Streptokinase, regarded as the most affordable antithrombotic enzyme, was not prescribed during the period under study. With the growing opportunities for enzymes for therapeutics, the use of enzyme-containing products which are comparatively expensive require cost-effectiveness studies.